(untitled) (Research, Society and Development, 2022)
This article will bring a brief study about the elements of the fourth industrial revolution and how people are preparing for these changes mainly for the job market. The term Industry 4.0 or fourth industrial revolution arises in Germany, it represents the change in the productive processes of companies making use of technology to integrate people and machines. Some terms are used when conceptualizing Industry 4.0 and all are increasingly present in our daily lives such as big data, robots, simulation, augmented reality, systems integration, additive manufacturing, cybersecurity, cloud, internet of things. The development of human capital and knowledge management are the key points that represent the success or failure of a company that intends to enter this revolution. Along with the concept of Industry 4.0, the following article addresses topics that are related to the proposed subject, namely: human capital, innovation and knowledge management. The methodology used to prove this work was a quantitative exploratory research. One of the important points to be noted is that a large part of the population is still unaware of the term Industry 4.0, so we can see that companies still have a long way to go so that their employees are prepared for the changes that are coming. happening and what will happen in the future.